ANTIMICROBIAL SUSCEPTIBILITY OF SALMONELLA SPP. ISOLATED FROM DOMESTIC ANIMALS IN VILLA CLARA PROVINCE, CUBA - Vega-Hernández, Marta (2020)
The emergency of antimicrobial resistance of Salmonella is a major concern worldwide, and recent studies highlight the relationship among antimicrobial consumption by animals and the diverse resistance mechanisms developed by microorganisms. Th is study was undertaken to investigate the circulation of Salmonella spp. associated with infectious processes in domestic animals as well as the patterns of susceptibility to antimicrobials. Sampling and Salmonella spp. isolation were carried out in the Department of General Bacteriology at the Provincial Veterinary Diagnostic Laboratory of Villa Clara province, Cuba, during 2016. The antimicrobial susceptibility was tested by the Kirby-Bauer method. Results were analyzed by the statistical package Statgraphics Centurion version XV-II/2006 applying descriptive procedures, and multiple comparisons of proportions, for the evaluation of the percentages of resistance of Salmonella by animal species and by serogroup. Th ere were identifi ed 46 Salmonella spp. isolates belonging to serogroups B, C1, C2 and D in 15% of samples, all coming from hens, bovines, sheep and pigs. In general, the antimicrobial resistance profi les were expressed for ampicillin (46% of isolates), sulphonamide compounds (28%), nalidixic acid (26%) and tetracycline (22%); resistance to ciprofl oxacin, gentamicin and cefotaxime were not detected. Th e most resistant Salmonella spp. isolates were from serogroups B and D, as well as those coming from sheep and pigs.